Gabe Halak Batak; Batak Toba Ethnic Bodiedness Traditions as a Reference for Actor Training - Ilham Rifandi; Ifwanul Hakim; Nazlah Syahaf Nasution (Gondang: Jurnal Seni dan Budaya, 2023)
Gabe Halak Batak is a term that was born from research on the bodiedness traditions of the Batak Toba people which means "Being a Batak Person". This research was conducted to take advantage of the bodiedness traditions of the Batak Toba Ethnic Community, one of which is Tortor. The author's interest in the tortor is because there are basic techniques in the tortor which are named metaphorically and through this naming can be an 'entrance' for actors in the process of exploring their physiology. In this study, the authors implemented it for actors from the Aka Bodi Theatre group in Medan who came from three different ethnicities. This study uses ethnographic and autoethnographic approaches in collecting data and interrogating the process of physiological exploration applied to acting training at the Aka Bodi Theatre. The results obtained are that each actor who participates in the training process experiences a variety of sensitivities related to the Batak Toba ethnic culture and has visual references regarding the creation of actions in the training.